Assessing temperature‐based adaptation limits to climate change of temperate perennial fruit crops. Issue 9 (16th February 2023) - Meza, Francisco; Darbyshire, Rebecca; Farrell, Aidan; Lakso, Alan; Lawson, James; Meinke, Holger; Nelson, Gerald; Stockle, Claudio
Abstract: Temperate perennial fruit and nut trees play varying roles in world food diversity—providing edible oils and micronutrient, energy, and protein dense foods. In addition, perennials reuse significant amounts of biomass each year providing a unique resilience. But they also have a unique sensitivity to seasonal temperatures, requiring a period of dormancy for successful growing season production. This paper takes a global view of five temperate tree fruit crops—apples, cherries, almonds, olives, and grapes—and assesses the effects of future temperature changes on thermal suitability. It uses climate data from five earth system models for two CMIP6 climate scenarios and temperature‐related indices of stress to indicate potential future areas where crops cannot be grown and highlight potential new suitable regions. The loss of currently suitable areas and new additions in new locations varies by scenario. In the southern hemisphere (SH), end‐century (2081–2100) suitable areas under the SSP 5–8.5 scenario decline by more than 40% compared to a recent historical period (1991–2010). In the northern hemisphere (NH) suitability increases by 20% to almost 60%. With SSP1‐2.6, however, the changes are much smaller with SH area declining by about 25% and NH increasing by about 10%. The results suggest substantial restructuring of global production for these crops. Essentially, climate change shifts temperature‐suitable locations toward higher latitudes. In the SH, most of the historically suitable areas were already at the southern end of the landmass limiting opportunities for adaptation. If breeding efforts can bring chilling requirements for the major cultivars closer to that currently seen in some cultivars, suitable areas at the end of the century are greater, but higher summer temperatures offset the extent. The high value of fruit crops provides adaptation opportunities such as cultivar selection, canopy cooling using sprinklers, shade netting, and precision irrigation. Abstract : Temperate perennial fruit and nut trees have a unique sensitivity to seasonal temperatures, requiring a period of cold for productive growth in the new season. Climate change impacts will shift suitable locations toward the poles with northern hemisphere changes greatest. Research that reduces chill requirements while retaining desirable characteristics can reduce the loss of suitable areas.